Edukasi Pencegahan Perilaku Bullying Melalui Video Pendek pada Siswa SMP Khairul Imam Medan - Nilam Sari; Heryanto Heryanto; Lorena Peranginangin; Renatal Halomoan Lumban Tobing (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Bullying in linguistic terms is bullying, which means disturbing and causing trouble. Bullying is an act that violates human rights, and currently, bullying cases are a hot topic being discussed in various media. Bullying is a serious act that affects children all over the world, including in Indonesia. Formal educational institutions, especially schools, are often places where bullying behaviour occurs. This phenomenon is not only limited to the lower middle school level, but upper middle school students are also not free from this act of bullying. In this context, junior high school students have begun to form groups and interact with their peers, making them more vulnerable to bullying. Therefore, the aim of this community service activity is to increase the knowledge of junior high school students, especially in class VIII at the Khairul Imam Medan Integrated Islamic Middle School, about bullying behavior. Educational activities were carried out three times, which included preparation, implementation, and evaluation stages. This education has benefits in efforts to prevent and detect early bullying behaviour in junior high school students, especially at Khairul Imam Integrated Islamic Middle School, Medan. Following the implementation of educational activities, we can conclude that students who were previously unaware of bullying now understand the concept and strategies to prevent it. The hope is that after this community service activity, the school and other related parties can take steps to prevent and detect bullying behaviour early, especially among junior high school students.